Evaluation of Moisture Susceptibility for Modified Open Graded Friction Course Mixes Used Styrene Butadiene Styrene - Ahmed, Miran Bahyam; Abed, Alaa Hussein; Al-Badran, Yasir Mawla Hammood (Al-Nahrain Journal for Engineering Sciences, 2019)
Open-graded-fraction-course (OGFC), is a hot asphalt mixture usually utilized as a private purpose wearing course, because of open graded asphalt mixture and aggregates skeleton (stone-on-stone) contact, it contain a relatively high air voids’ percentage, after compaction which are permeable to water. In this research one type of gradation was used (12.5 mm) NMAS, to preparing the OGFC asphalt mixtures, penetration grade 40/50, crushed aggregate, asphalt content prepared with 4 % and up to 6 % by weight of mixture with 0.5 % increments. Optimum asphalt content (OAC) was selected based on these criteria, air voids content, asphalt draindown, permeability, and abrasion resistance (aged and un-aged) condition. The mix performance had been investigated by indirect tensile strength and moisture susceptibility (sensitivity) measured according to the (AASHTO T283-14). Results illustrate that the increasing of asphalt binder content leads to a decrease of the air voids content, abrasion loss and permeability values, while draindown increase, conversely, the indirect tensile strength (ITS) had been significantly increased for both conditions and this is a gaod suggestion to resistance alongside moisture susceptibility. It can be decided that the increasing of asphalt  binder percent in OGFC asphalt mixture, leads to an increase in the thickness of binder coating around the aggregates. On the other hand, the influence of modifier that prepared with 4% styrene-butadiene-styrene (SBS) on OGFC asphalt mixture tends to improve the mix properties and exhibit higher (TSR) as compared with original asphalt by (31, 27.7 and 24.4) % at asphalt percent (4.8, 5.3 and 5.8) %, respectively. The SBS improved the adhesion between aggregate and asphalt which leads to reduce stripping of HMA, horizontal deformation, and increased the tensile stiffness modulus value.